2018
DOI: 10.5041/rmmj.10353
|View full text |Cite
|
Sign up to set email alerts
|

Screening to Detect Precursor Lesions of Pancreatic Adenocarcinoma in High-risk Individuals: A Single-center Experience

Abstract: Objective of the workPancreatic cancer (PC) is a deadly disease that is most commonly diagnosed at an incurable stage. Early diagnosis is the most important factor for improving prognosis. Evidence is beginning to accumulate that screening and surveillance may lead to the early detection of precursor lesions and/or pancreatic cancer in asymptomatic individuals. Proper screening methods and identification of such precursor lesions may enable effective pre-emptive interventions to prevent further fatalities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…These lesions are characterized by their cystic nature, mucin secretion and are less common than PanINs [ 29 ]. Studies on HRIs indicate that cystic lesions, particularly branch-duct (BD) type IPMN, are the most commonly diagnosed abnormalities during pancreatic cancer surveillance [ 30 37 ]. This occurrence is not unusual, considering the high prevalence of IPMNs, which can reach up to 11.3–25% among the general population aged ≥ 55 years and increases with age [ 38 , 39 ].…”
Section: Objective and Targets Of Pancreatic Cancer Surveillancementioning
confidence: 99%
“…These lesions are characterized by their cystic nature, mucin secretion and are less common than PanINs [ 29 ]. Studies on HRIs indicate that cystic lesions, particularly branch-duct (BD) type IPMN, are the most commonly diagnosed abnormalities during pancreatic cancer surveillance [ 30 37 ]. This occurrence is not unusual, considering the high prevalence of IPMNs, which can reach up to 11.3–25% among the general population aged ≥ 55 years and increases with age [ 38 , 39 ].…”
Section: Objective and Targets Of Pancreatic Cancer Surveillancementioning
confidence: 99%
“…No complications were noted in the 1 patient in our study who underwent surgery. Six studies reported adverse events from pancreatic surgery in patients undergoing screening, with a pooled event rate of 19% (95% CI 7.4%-43.4%) (24,25,27,30,32,33).…”
Section: Pancreasmentioning
confidence: 99%
“…La cohorte con Peutz-Jegher mostró un mayor riesgo (10%). El segundo estudio es israelí y en él evaluaron la factibilidad del escrutinio con ultrasonido endoscópico de los pacientes de alto riesgo para cáncer de páncreas 2 . Se incluyeron 123 pacientes evaluados entre 2008 y 2018 de forma anual o bienal.…”
Section: Escrutinio De Cáncer De Páncreasunclassified